Efficient Gap-Free Broadband Terahertz Generators Based on New Organic Quinolinium Single Crystals - Shin, Myeong Hoon; Kim, Won Tae; Kim, Se In; Lee, Seung Heon; Yu, In Cheol; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2019)
New organic electro-optic crystals containing orthogonally oriented electron-withdrawing groups are developed for efficient and gap-free THz wave generation with a very flat broadband spectral shape. These crystals consist of 2-(4-hydroxystyryl)-1-methylquinolinium (OHQ) cationic chromophores and nonplanar 4-(trifluoromethoxy)benzenesulfonate (TFO) anions with orthogonally oriented highly electronegative trifluoromethoxy groups capable of strong hydrogen bonds. OHQ-TFO crystals exhibit enhanced macroscopic optical nonlinearity with a second harmonic generation efficiency 2.3 times greater than that of benchmark OHQ-based crystals with conventional planar anions. This enhancement is attributed to reduced edge-to-face π–π interactions between cations and anions due to the orthogonal orientation and electron-withdrawing characteristics of trifluoromethoxy groups. Moreover, OHQ-TFO crystals exhibit excellent THz wave characteristics generated by optical rectification; 0.52 mm thick OHQ-TFO crystal generate a peak-to-peak THz electric field 15 times higher than that of inorganic standard 1.0 mm thick ZnTe crystal and a broader spectrum with an upper cut-off frequency near 8 THz at pump wavelengths of 1140–1500 nm. Unlike previously reported state-of-the-art organic electro-optic salt crystals with strong phonon absorption in the frequency range of 0.8–3 THz, OHQ-TFO crystals facilitate gap-free broadband THz wave generation without strong absorption modulations due to the strong hydrogen bond ability of trifluoromethoxy groups.
Keywords: Electron withdrawing group; Electronwithdrawing; Electrooptic crystals; Optical nonlinearity; Optical rectifications; Organic crystal; Orthogonal orientations; Second harmonic generation efficiencies; electro-optics; nonlinear optics; organic crystals; terahertz waves